Real world analysis of the efficacy and safety of eribulin compared to utidelone in combination with capecitabine for the treatment of metastatic breast cancer - Mengya Feng; Pingping Bi; Yihua Kang; Dechun Yang; Shengnan Ren; Xianping Lu; Guojian Xie; Hai Lei; Dan Mo (Cancer Cell International)
Abstract Background The objective of this study was to compare the efficacy and safety of subsequent chemotherapy with single eribulin or utidelone combined with a capecitabine regimen in patients with advanced breast cancer who had previously been treated with anthracyclines and paclitaxel. Methods This work was a retrospective analysis of 85 patients from July 2018 to July 2023. Forty-two and 43 patients were treated with the eribulin regimen and the utidelone/capecitabine regimen, respectively. The endpoints included progression-free survival, overall survival, the objective remission rate and safety. Survival analyses and multifactorial analyses were performed via the Kaplan‒Meier method, log-rank test and Cox regression models. Results As of 15 April 2024, the mPFS durations of the patients in the utidelone/capecitabine and eribulin treatment groups were 7.7 and 5.2 months, respectively, and the mOS durations were 22.0 and 18.2 months, respectively. Subgroup analyses revealed that in advanced first-line therapy, the mPFS durations of the utidelone/capecitabine group and the eribulin group were 11.8 and 7.0 months, respectively, and this difference was significant. In the eribulin treatment arm, the mPFS of first-line therapy was 7.0, whereas it was 3.3 months for posterior-line therapy, and this difference was significant. The most common adverse reactions were neurotoxicity, hand‒foot syndrome, hematological toxicity, gastrointestinal toxicity, and abnormalities in hepatic and renal functions. Conclusions In conclusion, either utidelone/capecitabine or eribulin chemotherapy may result in a survival benefit with a tolerable adverse effect profile and favorable safety profile in patients with metastatic breast cancer. The first-line use of eribulin resulted in better PFS and ORR than posterior-line use, and the combination of utidelone/capecitabine represents a more efficacious approach in the advanced first-line therapy of breast cancer.